Clinical PET Principles and Applications - Kim, E. Edmund; Lee, Myung-Chul; Inoue, Tomio; Wong, Wai Hoi (Springer New York, 2004)
With contributions from leaders in the PET community, the book is a valuable overview of the basic principles and clinical applications of PET. Emphasis is placed on the familiarization of normal distribution, artifacts, and common imaging agents such as FDG in conjunction with CT, MRI, and US to establish the clinical effectiveness of PET. Practical understanding of updated PET scanners, image process and quantification of PET measurements is also discussed. The book is divided into two sections, with the first 7 chapters dealing with the basic principles of PET for instrumentation, fusion, radiopharmaceuticals, radiosynthesis, safety and cost analysis, and the following 16 chapters focusing on the clinical techniques and indications of PET. There is also a unique atlas as well as comprehensive coverage on essential clinical PET studies in neurology, cardiology and oncology. As PET continues to undergo spectacular growth in the fields of nuclear medicine, radiology, and oncology, "Textbook of Clinical PET" is meant to provide a practical guide that helps nuclear medicine practitioners, radiologists, oncologists, and neurologists navigate the complexity of PET interpretation